Assessment of the potential effect of some streams properties on the isolated Aeromonas hydrophila strains susceptibility against some β-Lactams and Sulfamids - Mbiada, J. Signe; Djimeli, C. Lontsi; Njoya, A. Manouore; Eheth, J.S.; Tchakonté, S.; Arfao, A. Tamsa; Bessa, H. Ateba; Bricheux, G.; Nola, Moïse; Sime-Ngando, T. (Research in Biotechnology, 2015)
The isolation and characterization of A. hydrophila strains were carried out a given stream located in the equatorial zone in Cameroon (Central Africa), during the mild rainy season and the mild dry season. The water physicochemical parameters measured were temperature, pH, electrical conductivity, color, turbidity and suspended solids. It has been noted that bacterial abundances as well as the values of physicochemical parameters undergoes temporal variations. Antimicrobial susceptibility tests showed that the means diameters of inhibition with Oxacillin, Ceftriazone, Penicellin, Sulfamethoxazol-trimethoprim, Chloramphenicol, Imipenem, Amoxicillin-Clavulanic acid and Cefazolin were 6.44, 21, 6.63, 9.58, 15.37, 22.18, 14.29 and 10.26 mm respectively. 100% of strains tested were resistant to Penicillin, 89.47 % resistant to Oxacillin, 68.42% resistant to Sulphamethoxazole-trimetroprim and 63.15% were resistant to Cefazolin. There were 54.60% cases of antibiotic resistance, 24.34 % of intermediate sensitivity and 21.05% of sensitive strains against the tested antibiotics. The encoded redundancy analysis indicates that the percentage of the variation explained on the canonical axes is of 47.8% for the F1 axis and 25.9% for the F2 axis, for an accumulated percentage of 73.7%. The suspended solids, the Ceftriazon and Chloramphenicol are correlated to the F1 axis in positive coordinates, and the Temperature and Amoxicillin-Clavulanic acid in negative coordinates. The correlation test between the water physicochemical characteristics and the inhibition diameters of antibiotics showed some significant correlations (P<0.05). The regulation of bacterial genes would be regulated by complex mechanisms. Although many factors implied are linked to the bacterial cell, others may belong to the closed environment.